ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI DALAM PENGAMBILAN SERTIFIKASI AKUNTANSI: (Studi Empiris Mahasiswa Jurusan Akuntansi Universitas Se Karesidenan Surakarta) - Arkan, Ahmad Nazhifa; Witono, Banu (JURNAL ILMIAH EDUNOMIKA, 2025)
Accounting certification is a certificate that certifies that an accountant has credible skills and abilities in the field of accounting. Accounting certification has an important role for accountants who want to improve their qualifications and careers as professional accountants. This study aims to analyze the effect of career motivation, quality motivation, economic motivation and perceived educational costs on accounting students' interest in taking accounting certification. The population in this study were students of Accounting study programs at State Universities (PTN) and Private Universities (PTS) in the Surakarta karesidenan. This research sampling technique uses convenience sampling. The data source in the study used primary data obtained from questionnaires distributed to students of Accounting study programs at State Universities (PTN) and Private Universities (PTS) in the Surakarta karesidenan.The data analysis technique used is multiple regression analysis with the SPSS 25 program. The results showed that the variables of career motivation and perceived educational costs had an effect on the interest of accounting students in taking accounting certification, while quality motivation and economic motivation had no effect on the interest of accounting students in taking accounting certification. Keywords : interest in taking accounting certification, career motivation, quality motivation, economic motivation, perceived cost of education